The Influence of Affiliate Marketing, Online Reviews, and Product Knowledge on Skincare Purchase Decisions on TikTok Shop - Fiya Farha Kholida; Audita Nuvriasari (Economic and Business Horizon, 2026)
The intensifying competition within the skincare industry has encouraged businesses to optimize digital marketing strategies in order to attract consumer attention and influence purchasing decisions on e-commerce platforms. TikTok Shop, as a rapidly growing digital marketplace, provides a relevant context for examining contemporary consumer behavior. This study aims to analyze the effects of affiliate marketing, online customer reviews, and product knowledge on purchasing decisions for skincare products on TikTok Shop. A quantitative approach was employed using purposive sampling, involving 100 respondents identified using the Lemeshow formula. Data were analyzed using multiple linear regression, and hypotheses were tested through t-tests. The findings reveal that affiliate marketing does not have a significant effect on purchasing decisions. In contrast, online customer reviews and product knowledge demonstrate positive and statistically significant influences. These results emphasize that the credibility of online reviews and consumers’ understanding of product attributes are critical determinants in shaping purchasing decisions within competitive digital commerce environments.